2021
DOI: 10.1002/smll.202101638
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Plasmonic Photocatalysis Based on TiO2 and Noble Metal Nanoparticles for Energy Conversion, Environmental Remediation, and Organic Synthesis

Abstract: Scheme 1. Different strategies and concepts employed in the design and development of photocatalysts based on a semiconductor, such as TiO 2 , and plasmonic NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
168
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(170 citation statements)
references
References 422 publications
(529 reference statements)
2
168
0
Order By: Relevance
“…In this way, they will be more competitive in the market than P25 that has been put into practical use. 234,235 As for CO 2 reduction, in addition to nano-particle photocatalytic systems, attention should also be paid to building flexible PM photoelectrodes or photovoltaic systems. While ensuring the conversion rate and selectivity of CO 2 reduction, the system can also be made into a shape that is conducive to capturing CO 2 in the atmosphere and separating some reduction products by using their flexible characteristics.…”
Section: Current Challenges and Future Prospectsmentioning
confidence: 99%
“…In this way, they will be more competitive in the market than P25 that has been put into practical use. 234,235 As for CO 2 reduction, in addition to nano-particle photocatalytic systems, attention should also be paid to building flexible PM photoelectrodes or photovoltaic systems. While ensuring the conversion rate and selectivity of CO 2 reduction, the system can also be made into a shape that is conducive to capturing CO 2 in the atmosphere and separating some reduction products by using their flexible characteristics.…”
Section: Current Challenges and Future Prospectsmentioning
confidence: 99%
“…and metal sulfides (CdS, MoS 2 , etc. ) are widely studied as the photocatalysts ( Kumar et al., 2021 ; Kusiak-Nejman et al., 2021 ; Premaratne et al., 2004 ). As discussed in section atomic layer deposition method , by creating defect sites (i.e., O-defect, S-defect), the metal-oxides- and metal-sulfides-based SAPs can be easily synthesized by the atom trapping methods.…”
Section: Current Research Progress On Sapsmentioning
confidence: 99%
“…[30,31] It is known that the building of semiconductor (TiO 2 ) and precious metal com posites is an effective method to modify the charge transfer kinetics of semiconductors. [32][33][34] Our previous work reported that AgTiO 2 core-shell nanostructures exhibited much higher photocatalytic activity than bare TiO 2 films because of the efficient carrier transfer at the AgTiO 2 interface by exposure ultraviolet light. [35] Zhang et al fabricated a mixed phase of anatase/rutile TiO 2 by a twostep hydrothermal method then deposited plasmonic Ag nanoparticles on the heterostructure surface to construct the anatase/rutile TiO 2 Ag hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30,31 ] It is known that the building of semiconductor (TiO 2 ) and precious metal composites is an effective method to modify the charge transfer kinetics of semiconductors. [ 32–34 ] Our previous work reported that Ag‐TiO 2 core–shell nanostructures exhibited much higher photocatalytic activity than bare TiO 2 films because of the efficient carrier transfer at the Ag‐TiO 2 interface by exposure ultra‐violet light. [ 35 ] Zhang et al.…”
Section: Introductionmentioning
confidence: 99%